2021
DOI: 10.3389/fimmu.2021.789610
|View full text |Cite
|
Sign up to set email alerts
|

PANoptosis: A New Insight Into Oral Infectious Diseases

Abstract: The oral microbiome, one of the most complex and intensive microbial ecosystems in the human body, comprises bacteria, archaea, fungi, protozoa, and viruses. Dysbiosis of the oral microbiome is the initiating factor that leads to oral infectious diseases. Infection is a sophisticated biological process involving interplay between the pathogen and the host, which often leads to activation of programmed cell death. Studies suggest that pyroptosis, apoptosis, and necroptosis are involved in multiple oral infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 108 publications
0
24
0
Order By: Relevance
“…With the release of death-associated molecular patterns, necroptotic cells can transmit danger signals and activate inflammatory responses. Macrophages are important mediators of host inflammatory responses to infection ( 20 ). In the current study, we found abundant macrophage infiltration in periapical lesion specimens from RAP-diagnosed patients as well as from an experimental RAP model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the release of death-associated molecular patterns, necroptotic cells can transmit danger signals and activate inflammatory responses. Macrophages are important mediators of host inflammatory responses to infection ( 20 ). In the current study, we found abundant macrophage infiltration in periapical lesion specimens from RAP-diagnosed patients as well as from an experimental RAP model.…”
Section: Discussionmentioning
confidence: 99%
“…PANoptosis, a newly emerging concept highlighting the cross talk and coordination between pyroptosis, apoptosis, and necroptosis, has been proposed ( 34 ). Recently, we have reviewed the functional consequences and activation mechanisms of PANoptosis in oral infectious diseases ( 20 ). E. faecalis infection can induce pyroptosis, apoptosis, and necroptosis of macrophages based on previous and current studies ( 18 , 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis has been the subject of intensive research in the past three decades while pyroptosis has become ahot trend in recent years. Therefore, with the concept of pan-apoptosis (PANoptosis), the research prospect of necroptosis is foreseeable as the last link of the triangle relationship [ 57 , 58 ]. PANoptosis is amultifaceted immune response with important pathophysiological implications for infectious diseases, autoimmunity, and cancer, reflecting the complexity of host responses to pathogens and the interconnectedness of signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…PANoptosis is modulated by the multi-protein PANoptosome complex, which provides a molecular scaffold for simultaneous engagement of key molecules from pyroptosis, apoptosis and necroptosis (107). According to the biological functions, compositions of the PANoptosome consist of sensors, adaptors and catalytic effectors in general, such as Z-DNA binding protein 1 (ZBP1), FADD and caspase-1, respectively (108). Since PANoptosis has been triggered during various pathogenic infections, autoinflammatory diseases and cancer (107), indicating that it has significant pathophysiological relevance.…”
Section: Pyroptosis-related Panoptosis In Gutmentioning
confidence: 99%